Pengaruh Pemberian Terapi Musik Klasik Terhadap Penurunan Dismenore Primer Pada Remaja Putri Di SMA Negeri 1 Buton - Mida, Alhamida Salnaf Ituga; Taqiyah, Yusrah; Agustini, Tutik (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Menorrhea during menstruation, unpleasant experiences of sensations and emotions, circumstances that exhibit subjective/individual discomfort, hurt the body, and whenever individuals say it is real. If the dismenmenore is not handled it can affect the activities and attitudes of the students. One of the non- pharmacological measures in dealing with pain is the technique of distraction with music therapy that can safely reduce pain. Listening to music can produce zatendorphins (a substance similar to morphine supplied by the body that can reduce pain that can inhibit the transmission of pain impulses in the central nervous system, so that the sensation of menstrual pain can be reduced. The purpose of this study was to find out the effect of classical music therapy on the reduction of primary dismenorrhea pain in young women of SMAN 1 Buton. This research uses experimental methods, using pre-experimental designs with pretest-postest designs. In this study using non probability sampling with consecutive sampling method, the population in this study was all girls who experienced primary dismenorrhea in xli ipa1, IPA2 and IPA3 classes of 35 people. The data analysis used is univariate and bivariate, where bivariate uses Wilcoxon test analysis. Instruments used numeric rating scale (NRS). Samples were given classical music therapy 10-20 minutes for 3 consecutive days. The results showed a value of Ï = 0.000, where the Ï value is smaller than Î±=0.05 then Ha is accepted and H0 is rejected. Thus, it can be concluded that there are different results before and after the administration of classical music therapy, so there is an effect of effective classical music therapy on disminore. While the advice from this study is to address menorrhea pain not directly taking pharmacological drugs but rather using musical therapies such as classical music therapy, then this study can also be an additional reference related classical music therapy to menstrual pain.